URBAN MICROCLIMATE IN VEGETATED AND NON-VEGETATED AREAS IN RAINY AND SUNNY CONDITIONS - Souza, Roberta Daniela; Novais, Jonathan Willian Zangeski; Pierangeli, Maria Aparecida Pereira; Lanssanova, Michelle Danielle; Fernandes, Thiago .; Hoki, Vanusa Souza Pacheco; Souza, Pricila Juliana (Ra'e Ga: o Espaço Geográfico em Análise, 2020)
Cuiabá city is nationally known as "green city" because of to its large afforestation, has experienced progressive urban expansion for years, with deforestation possibly causing a rise in temperature and the development of heat islands In this context the afforestation can be an alternative for the improvement of the thermal comfort of the residents of this city. So the study objective was to analyze the microclimate differences of vegetated and non-vegetated urban areas in rainy and sunny conditions, analyzing also the heat index and the thermal discomfort index. The sampling took place at a public place and great flow of pedestrians. Data on the air temperature (Tair), soil temperature (Ts), and relative air humidity (Rh) were recorded using two linear transects, starting at 7 am and ending at 7 pm, in two-hour intervals. Due to the seasonality of the city's climate, measurements were taken in the dry and humid period of the year. There was a statistical difference for soil temperature between the sites (p-value < 0.001) and an increase of approximately 10°C in both periods in non-vegetated areas. There was no statistically significant difference for the heat index and thermal discomfort index among the analyzed transects, especially in the wet season, periods of discomfort occurred. Was verified that for open sites vegetation decreased air and soil temperature, increased relative humidity, but it was not enough to have thermal comfort at all times of the day.